علم النحو المتقدم لأغراض علمية (al-Nahu al-Arabi al-mutaqaddim li-aghradh ilmiyyah min khilal al-Quranul karim) - Dollah, Nafi@Hanafi (IIUM Press, 2004)
To study about Advanced Arabic Grammar For Academic Purposes : Dirasat Fi al-Jumlah al- Ismiyyah Min Khilal Shawahid al- Qur'an.